2017
DOI: 10.1016/j.fsigen.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age prediction based on DNA methylation: Massive parallel sequencing and random forest regression

Abstract: The use of DNA methylation (DNAm) to obtain additional information in forensic investigations showed to be a promising and increasing field of interest. Prediction of the chronological age based on age-dependent changes in the DNAm of specific CpG sites within the genome is one such potential application. Here we present an age-prediction tool for whole blood based on massive parallel sequencing (MPS) and a random forest machine learning algorithm. MPS allows accurate DNAm determination of pre-selected markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
138
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 45 publications
15
138
0
6
Order By: Relevance
“…In this study of Naue et al. , all the analyzed markers in blood ( DDO , ELOVL2 , F5 , GRM2 , HOXC4 , KLF14 , LDB2 , NKIRAS2 , RPA2 , SAMD10 , TRIM59 , MEIS1, and ZYG11A ) showed a comparable age dependency in comparison to a previous study using whole blood of living individuals . Interestingly, the ELOVL2 position (Chr6: 11044644; cg16867657) showed a Pearson correlation coefficient of 0.88, which is similar to the value ( r = 0.76) obtained in our data for the same position (CpG6).…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…In this study of Naue et al. , all the analyzed markers in blood ( DDO , ELOVL2 , F5 , GRM2 , HOXC4 , KLF14 , LDB2 , NKIRAS2 , RPA2 , SAMD10 , TRIM59 , MEIS1, and ZYG11A ) showed a comparable age dependency in comparison to a previous study using whole blood of living individuals . Interestingly, the ELOVL2 position (Chr6: 11044644; cg16867657) showed a Pearson correlation coefficient of 0.88, which is similar to the value ( r = 0.76) obtained in our data for the same position (CpG6).…”
Section: Discussionsupporting
confidence: 41%
“…The cross‐validation of the training set leads to a MAD of 7.22 years and evaluation of model performance using an independent test set of 19 individuals showed a MAD of 8.84 years. Previous forensic studies, most of them with blood samples of living individuals, using different loci and different number of markers, covering different age ranges and using different methodologies, gave values of MAD between 3.5 to 7.5 years . Thus, in our study the obtained MAD value, although less accurate, is in the range of other research approaches.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…With the emergence of MPS in the forensic community, more recent research is going to focus on this new method [38]. Based on a selection of age-informative CpG sites using publicly available methylation data from 1,156 whole blood samples (2–90 years), Vidaki et al [31] applied stepwise regression for variable selection and identified 23 CpG sites that provided an age prediction accuracy of 0.92 (MAD ±4.6 years).…”
Section: Markers and Methods To Estimate Human Chronological Agementioning
confidence: 99%